(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
Infectious diseases such as smallpox, tuberculosis and leprosy have all invaded rural Nigeria at periods when colonial hegemons assume supremacy over indigenous knowledge systems. The most recent infectious disease, Coronavirus Disease 2019 (COVID-19), spread within an interconnected world in manners that exposed the false assumption that the global North has all the expertise and solutions to salvage devastating health, economic and social impacts of infectious diseases. Adopting a historical research approach which engaged archival records and intergenerational dialogues in Esham, Ekporinya (Ekajuk Kingdom); Egbe, Ndum (Mbube); Bansan-Osokom, Borum, Okundi, Katchuan (Boki); Ishibori (Ogoja); this article argues that responses to infectious diseases’ emergencies in rural Nigeria are firmly enmesh in forms of belittlement and exclusion of the narrative autonomy of the people to handle infectious diseases’ emergencies. Findings coalesce to indicate that the ‘capacity approach’ in handling infectious diseases’ emergencies in rural Nigeria is characterized by discernible secrecy; it is non-curative, urban-based and aims at serving the medical needs of ‘very important personalities’ (VIPs), their immediate dependents and servants. The article concludes that capacity building for community health workers to facilitate community-led solutions to infectious diseases’ emergencies, particularly COVID-19, only spearheads local level behavioural changes without capacitating local community influencers and leaders on how public health practices, from epidemiological modelling to outbreak containment, help to perpetuate global inequalities. Hence, public health only manages and maintains global health inequity. Consequently, capacity building to facilitate indigenous or community-led solutions to infectious diseases’ emergencies in rural Nigeria should be focus at unsettling webs of meaning and power in global health; rather than just interrogating local social norms, attitudes, behaviours and practices.